Food safety training and foodservice employees' knowledge and behavior. - Roberts, Kevin R.; Barrett, Betsy B.; Howells, Amber D.; Shanklin, Carol W.; Pilling, Valerie K.; Brannon, Laura A. (International Association for Food Protection, 2008)
Statistics show that 59% of foodborne illnesses are traced to restaurant operations. Food safety training has been identified as a way to assure public health, yet evidence supporting the effectiveness of training has been inconclusive. A systematic random sample of 31 restaurants in three midwestern states was selected to assess the effect of training on food safety knowledge and behavior. A total of 402 employees (242 pretraining and 160 post-training) participated in this study. Pre and post-training assessments were conducted on knowledge and behavior related to three key food safety practices: cross contamination, poor personal hygiene, and time/temperature abuse. Overall knowledge (P ≥ .05) and compliance with standards of behavior (P ≥ .001) improved significantly between pre- and post-training. When each practice was examined independently, only handwashing knowledge (P ≥ .001) and behavior (P ≥ .001) significantly improved. Results indicated that training can improve knowledge and behaviors, but knowledge alone does not always improve behaviors.
Keywords: Food safety; Training; Personal hygiene; Time/temperature abuse; Cross contamination; Foodborne illnesses